Quality Of Party Dresses With Embellishment Techniques Inspired By Cheongsam Tail - Arda Aprilia Anisa; Irmayanti Irmayanti (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to realize a party dress inspired by the silhouette of a Cheongsam tail through the application of embellishment techniques. The creative process was carried out through the stages of exploration, design, realization, and evaluation using a practice-led research approach. The research subjects consisted of 13 panelists, divided into 3 expert panelists and 10 trained panelists. The research object was a party dress product designed by the researcher. Data analysis was conducted using descriptive quantitative methods by calculating the percentage of product quality levels based on six assessment indicators, namely design, sizing, aesthetics, sewing techniques, garment performance, and uniqueness. The results indicate that the party dress applying embellishment techniques inspired by the Cheongsam tail silhouette achieved a mean score of 95%, categorized as very feasible. The product quality test results show that the party dress has an attractive design, appropriate sizing, a high level of aesthetics, good garment performance, neat sewing techniques, and a distinctive level of uniqueness, particularly in terms of the ornamental application of embellishment techniques. Thus, the design of this party dress produces innovative, distinctive, and character-driven works that are relevant to the development of the contemporary fashion industry.